DEVELOPING ELECTRONIC STUDENT-BASED PROBLEM WORKSHEET FOR PRIMARY SCHOOL STUDENT - Nissa'atul Syaidah; Silviana Nur Faizah (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
The shift from face-to-face learning to online learning during the COVID-19 pandemic has made printed teaching materials irrelevant. Teaching materials in online learning need to be designed to be more interactive in the form of electronic teaching materials in order to create two-way communication between teaching materials and students because online learning requires maximum learning autonomy from students. The irrelevance of existing teaching materials causes various learning problems in primary schools such as the teaching materials used do not encourage students' willingness to learn, some students experience learning backwards, and teachers need extra time to correct students' assignments. This study aims to develop electronic student worksheets based on Problem Based Learning (PBL) in primary schools. This development research refers to the ADDIE model as the model consists of systematic stages in an effort to solve learning problems according to the characteristics of the learner. The subjects of this study were 40 grade 3 students of Madrasah Ibtidaiyah (Islamic Primary School) Pembangunan Lamongan. The results showed 1) the validity of the electronic student worksheets in the very valid category based on the assessments of linguists, material experts, design experts, and learning experts, 2) The attractiveness of electronic student worksheets in the very interesting category. Based on the results of this study, the use of electronic student worksheets is appropriate to be used to support the thematic learning process.